Data supporting: 'Development of a thermal excitation source used in an active thermographic UAV platform' - Deane, Shakeb; Tsourdos, Antonios; Avdelidis, Nicolas P.; Zolotas, Argyrios; Maldague, Xavier P.; Ibarra-Castanedo, Clemente; Genest, Marc; Pant, Shashank; Williamson, Alex A.; Withers, Stephen; Ahmadi, Mohammadali (Cranfield University, 2022)
This work aims to address the effectivenessand challenges of using active infrared thermography (IRT) on-board an unmannedaerial vehicle (UAV) platform. The work seeks to assess the performance ofsmall low powered forms of excitation which are suitable for activethermography and the ability to locate subsurface defects on composites. Anexcitation source in the form of multiple 250 W lamps are mounted onto a UAVand are solely battery powered with a remote trigger to power cycle them.Multiple experiments address the interference from the UAV whilst performing anactive IRT inspection. The optimal distances and time required for a UAV inspection using IRT is calculated. Multiple signal processing techniques areused to analyse the composites which helps locate the sub-surface defects. It was observedthat a UAV can successfully carry the required sensors and equipment for anActive thermographic NDT inspection which can provide access to difficult areas. Most active thermographic inspection equipment is large, heavy, and expensive. Furthermore, using such equipment for inspection of complexstructures is time-consuming. For example, a cherry picker would be required toinspect the tail of an aircraft. This solution looks to assist engineersinspecting complex composite structures and could potentially significantly reduce the time and cost of a routine inspection.
Keywords: Manufacturing Robotics and Mechatronics (excl. Automotive Mechatronics)'; 'Aerospace Engineering'; 'Aerospace Materials'; 'Physical Chemistry of Materials'; 'Physical Sciences not elsewhere classified'